The estimation of fuzzy boundary of multioperational machine tool life - Andrey Kirillovich Tugengold; Konstantin Grigoryevich Shuchev; Andrey Igorevich Izyumov; Dmitry Yuryevich Terekhov (Advanced Engineering Research)
The purpose of this paper is to present the basic principles of the construction and operation of monitoring systems of the tool condition, and the machine tooling backup man-agement in the computer-aided manufacturing. The proposed approach is focused on creating conditions for the effective tool state management. For this, the application of the intelligent host control module on the basis of the interactive electronic technical documentation of the mechatronic technological object is proposed. Valuation principles of the tool life fuzzy boundary are fully considered on the basis of the of fuzzy knowledge theory. Three methods for estimating the parameters of the resistance fuzzy boundary are presented. A neural network which operates on the basis of the developed fuzzy prediction rule base of the cutting tool wear depending on the instrument status and its impact on the part cutting accuracy is built. The results obtained are applicable in the sphere of the industrial engineering.